Hafnium-doped hydroxyapatite nanoparticles with ionizing radiation for lung cancer treatment. (June 2016) - Chen, Min-Hua; Hanagata, Nobutaka; Ikoma, Toshiyuki; Huang, Jian-Yuan; Li, Keng-Yuan; Lin, Chun-Pin; Lin, Feng-Huei
Graphical abstract: Abstract: Recently, photodynamic therapy (PDT) is one of the new clinical options by generating cytotoxic reactive oxygen species (ROS) to kill cancer cells. However, the optical approach of PDT is limited by tissue penetration depth of visible light. In this study, we propose that a ROS-enhanced nanoparticle, hafnium-doped hydroxyapatite (Hf:HAp), which is a material to yield large quantities of ROS inside the cells when the nanoparticles are bombarded with high penetrating power of ionizing radiation. Hf:HAp nanoparticles are generated by wet chemical precipitation with total doping concentration of 15 mol% Hf 4+ relative to Ca 2+ in HAp host material. The results show that the HAp particles could be successfully doped with Hf ions, resulted in the formation of nano-sized rod-like shape and with pH-dependent solubility. The impact of ionizing radiation on Hf:HAp nanoparticles is assessed by using in-vitro and in-vivo model using A549 cell line. The 2′, 7′-dichlorofluorescein diacetate (DCFH-DA) results reveal that after being exposed to gamma rays, Hf:HAp could significantly lead to the formation of ROS in cells. Both cell viability (WST-1) and cytotoxicity (LDH) assay show the consistent results that A549 lung cancer cell lines are damaged with changes in the cells' ROS level. The in-vivo studies further demonstrate that the tumor growth is inhibited owing to the cells apoptosis when Hf:HAp nanoparticles are bombarded with ionizing radiation. This finding offer a new therapeutic method of interacting with ionizing radiation and demonstrate the potential of Hf:HAp nanoparticles in tumor treatment, such as being used in a palliative treatment after lung surgical procedure. Statement of Significance: Photodynamic therapy (PDT) is one of the new clinical options by generating cytotoxic reactive oxygen species (ROS) to kill cancer cells. Unfortunately, the approach of PDT is usually limited to the treatment of systemic disease and deeper tumor, due to the limited tissue penetration depth of visible light (620–690 nm). Here we report a ROS-enhanced nanoparticle, hafnium-doped hydroxyapatite (Hf:HAp), which can trigger ROS when particles are irradiated with high penetrating power of ionizing radiation. The present study provides quantitative data relating ROS generation and the therapeutic effect of Hf:HAp nanoparticles in lung cancer cells. As such, this material has opened an innovative window for deeper tumor and systemic disease treatment.